Stochastic motility energetics reveals cooperative bacterial swarming in optical tweezers - Clara Luque-Rioja; Horacio López-Menéndez; Macarena Calero; Niccolò Caselli; Diego Herráez-Aguilar; Juan Pedro G. Villaluenga; Francisco Monroy (Proceedings of the National Academy of Sciences, 2026)
Bacterial flagellar swarming enables dense microbial populations to migrate collectively across surfaces, often resulting in emergent, coordinated behaviors. However, probing the underlying energetics of swarming at the single-cluster level remains a challenge. Here, we combine optical tweezers and multiparticle tracking within a stochastic thermodynamic framework to characterize the active motility of confined Proteus mirabilis clusters. Using the photon momentum method to directly measure trapping forces, we show that swarming clusters generate persistent, dissipative flows indicative of nonequilibrium stationary motility within confined solenoidal mesostructures. These flagellar rotational dynamics break detailed balance in mesoscopic force space and exceed the limits of passive friction, as evidenced by force-velocity correlations and vortex-like circulations. By coarse-graining cluster trajectories into an active Brownian phase space, we quantify the work performed by bacterial swarms at cooperative coupling to thermal fluctuations, resulting in dissipative Ohmic-like currents overcoming conservative trapping. Our findings establish a generalizable approach to quantify collective motility and energetic dissipation in active bacterial clusters under confinement, offering insights into the physical principles governing microbial cooperativity.